ARCHIVAL STUDIES AT VILNIUS UNIVERSITY: DEVELOPMENT AND PERSPECTIVES - ZINKEVIČIENĖ, JULIJA (Knygotyra, 2012)
Todays’ approaches to the role of archives and their functions in society as well as requirements to them as social institutions and to professional archivists have changed essentially. Traditionally closed, difficult to access and self-oriented archives do not seem to be popular and promising anymore. World archives are more oriented towards the dissemination of information and satisfying the information needs of society and not only to the preservation of historical heritage. The European Union supports an integrated approach to memory and heritage information institutions, their interactions, related research and educational programmes. In addition, the archives of institutions and organizations co-exist with historical archives. They require information organization and management skills. Therefore, modern archivists need a high information competence, good knowledge of foreign languages and communication skills. The goal of the study was to analyse the development of the archival study programme, to explain the curent situation and to outline the future perspectives in the improvement of the programme. The author presents her insights developed while working with this programme from the very beginning of its development. The Faculty of Communication at the Vilnius University was the first in Lithuania to prepare and start implementing the bachelor study programme in archival work in 1999. The programme was created after winning the competition announced by the government of the Republic of Lithuania for the academic archival studies at the Lithuanian universities. The first study programme was compiled as a common programme run in cooperation with the Faculty of History at the VU. Archivists have been educated at the Faculty of Communication for fourteen years. The content of the study programme is being constantly modified, and this helps to improve the education. A permanent analysis of archival study programmes at foreign universities allows us to understand the study programme from multiple perspectives. Graduates of the archival study programme acquire skills in the organization and management of information in different cultural, scientific, business, governmental and media institutions as well as in special information services. They learn how to provide information to communites, create and implement information policy, carry out information and communication research. The goal of the programme is to provide the basic education of archivistics on the university level, knowledge of information and communication needed for professional activity in knowledge management and communicating with the professional environment and society from within archives of different types. The study options are implemented using the experience of lecturers at the Faculty of Communication and other departments, acquired in teaching the subjecs of documentary communication, history, humanitarian culture, foreign languages, etc. Contacts with state archives have been established, the cooperation with institutions in public and business sectors is going on. Agreements regarding the teaching of several courses on the basis of their activities have been reached, and professionals are providing specific teaching modules. There are advanced quality ensurance and environmental scanning systems implemented in the study programme. They should be improved using criteria accepted on the international level.